A case cohort study of suicide in relation to exposure to electric and magnetic fields among electrical utility workers. Issue 1 (January 1996) - Baris, D; Armstrong, B G; Deadman, J; Thériault, G
Abstract : OBJECTIVES–This case cohort study examines whether there is an association between exposure to electric and magnetic fields and suicide in a population of 21, 744 male electrical utility workers from the Canadian Province of Québec. METHODS–49 deaths from suicide were identified between 1970 and 1988 and a subcohort was selected comprising a 1% random sample from this cohort as a basis for risk estimation. Cumulative and current exposures to electric fields, magnetic fields, and pulsed electromagnetic fields (as recorded by the POSITRON meter) were estimated for the subcohort and cases through a job exposure matrix. Two versions of each of these six indices were calculated, one based on the arithmetic mean (AM), and one on the geometric mean (GM) of field strengths. RESULTS–For cumulative exposure, rate ratios (RR) for all three fields showed mostly small non-significant increases in the medium and high exposure groups. The most increased risk was found in the medium exposure group for the GM of the electric field (RR = 2.76, 95% CI 1.15-6.62). The results did not differ after adjustment for socioeconomic state, alcohol use, marital state, and mental disorders. There was a little evidence for an association of risk with exposure immediately before the suicide. CONCLUSION–Some evidence for an association between suicide and cumulative exposure to the GM of the electric fields was found. This specific index was not initially identified as the most relevant index, but rather emerged afterwards as showing the most positive association with suicide among the 10 indices studied. Thus the evidence from this study for a causal association between exposure to electric fields and suicide is weak. Small sample size (deaths from suicide) and inability to control for all potential confounding factors were the main limitations of this study.